Public and private sector’s management at Mekong river - DOCKTHAISONG, DR. BOONTON; THONGTHIP, DR. BOONRUEN; CHAMNINA, DR. EKACHAI; NOI, DR. ANUCHA CHANG (The journal of contemporary issues in business and government, 2021)
The objectives of this research are: 1) To study the management problems of Public and Private Sector’s management at Mekong River during 2020, 2) To study methods Procedures and processes of Public and Private Sector’s Management at Mekong River, and 3) To present the guidelines and recommendations for the management of Public and Private Sector’s Management at Mekong River. The qualitative research is employed to the data by documents analysis of document data, the researcher has studied and analysis from articles, textbooks, journals, online media and related research. The results of the study showed that: Management problems of Public and Private Sector’s management at Mekong River during 2020. The Public should pay more attention to the protection of impacts on people along the Mekong River. In order to make the management most efficient and have the least impact on people under today's extremely changing environment. Methods and management, The Basin Development Strategy BDS 2021-2030 should be established with stakeholders from 4 member countries: Cambodia, Laos, Thailand and Vietnam by collaborations from the Mekong River Commission, a civil society NGO Project developer and the Private sector participate and find guidelines and recommendations, The Creating a mechanism to drive water resources management approach Both at the policy level and at the local level This will be the beginning of a strong community network. Especially to alert and monitor the water situation in the area to Public agencies for the benefit of efficient water management planning methods procedures and processes.